2010
DOI: 10.1111/j.1095-8649.2010.02664.x
|View full text |Cite
|
Sign up to set email alerts
|

Validation of scale‐age determination in European grayling Thymallus thymallus using tag‐recapture analysis

Abstract: To validate age determination from scales in European grayling Thymallus thymallus, the scale-read age of fish was compared with the true age obtained by tag-recapture analysis. A total of 3997 individuals were tagged with visible implant tags and passive integrated transponder (PIT) tags in the River Wylye, south-west England during 1999-2007. Annual repeat surveys were undertaken and collected scales read without prior knowledge of tag-recapture age. Accuracy of fish ageing by scales was highest in 1 and 2 y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 23 publications
(31 reference statements)
0
7
0
Order By: Relevance
“…Anthropogenic pressure [32][33][34], including strong pressure from recreational fishing [35], progressing eutrophication and pollution of rivers [36][37][38], have led to a dramatic decline in European grayling populations throughout Europe. These observations are particularly important for European graylings aged 3 to 5 years, which are characterized by the highest reproductive potential, as well as individuals older than 5 years which account for up to 4% of the grayling population in many European regions [39,40]. For these reasons, the European grayling was classified as a conservation dependent (CD) species on the 2009 Red List of Fish and Lamprey Species [41].…”
Section: Introductionmentioning
confidence: 99%
“…Anthropogenic pressure [32][33][34], including strong pressure from recreational fishing [35], progressing eutrophication and pollution of rivers [36][37][38], have led to a dramatic decline in European grayling populations throughout Europe. These observations are particularly important for European graylings aged 3 to 5 years, which are characterized by the highest reproductive potential, as well as individuals older than 5 years which account for up to 4% of the grayling population in many European regions [39,40]. For these reasons, the European grayling was classified as a conservation dependent (CD) species on the 2009 Red List of Fish and Lamprey Species [41].…”
Section: Introductionmentioning
confidence: 99%
“…McMichael et al., 1998). Moreover, a previous study on grayling age analysis using Wylye survey data revealed individual recapture rates by electrofishing were sufficiently high to enable an age‐validation exercise (Horká et al., 2010), thus at least some individuals were surviving capture by electrofishing.…”
Section: Discussionmentioning
confidence: 99%
“…Biometric data were collected under light anaesthesia (2‐phenoxyethanol; 0.2 ml/L), with fish identified to species, and measured for fork length (nearest mm) and mass (to 0.1 g). A scale sample (three to five scales per fish) was taken from each grayling using sterilised instruments, from between the dorsal fin and lateral line, to enable age assessment while accounting for known bias in aging of older fish (Horká et al., 2010). Following their recovery to normal behaviour, all fish were released back alive into the river section where they were captured.…”
Section: Methodsmentioning
confidence: 99%
“…By comparison with such modern examples, the inner ring pattern of the scale (Fig. 7F) is loose and the outer concentric laminae are closely packed, indicating that the fish may have been only one year old when it died (Edgar, 1951;Horká et al, 2010).…”
Section: Anatomy Of Fishesmentioning
confidence: 99%